Vida após a morte: uma abordagem acerca da influência persa na origem da crença judaica na ressurreição, a partir do texto de Isaías 26,19. - Araujo Júnior, Geraldo Batista de (2018)
The belief in the idea that life has continuity after death is part of the representation of various religious traditions. However, this belief manifests itself in the most distinct sorts, being one of the most common, the idea that deads will resurrect. The religious mores which interest in this research, in its origins, accepted death as an absolute end for all human beings who thought of being doomed for a place designated by the Hebrew expression šü´ôl. A kind of underworld to which all descended and whose modest subsistence was a feeble mirror of practical reality or, depending on the text, a place of quietness. Nevertheless, as of the 6th century BC, the people who later became known as Jews experienced deportation under the domination of the Babylonians. Moreover, decades later, already under the rule of the Persian empire, we testified not only a return to the land of origin Judah though, above all a textual production not previously comprehended among Jews just like as the outbreak of belief in the resurrection of the dead. The research investigates the emergence of this belief within the Jewish worldview also evidences its dependence on the Iranian perspective from texts arising from the Zoroastrian tradition, especially the Gathas of Zarathustra. Of an interpretative nature, the research required analysis of sacred books of the First Testament – or of the Hebrew Bible – addressing some forms of interpretation of particular excerpts that are pertinent to the understanding the adoption of the belief in the resurrection from the dead. We are tied up in exegetical analyses of authors who adopt the approach of the historical-critical method such as Walther Eichrodt and Gerhard von Rad, but also the contributions of the phenomenology of religion from the texts of authors like Mircea Eliade were of capital importance. Also, we refer our dissertation to authors who disagree with the point of view advocated by the researcher, such as John J. Collins and James Barr. We believe that the results achieved are consistent with the proposed research and that the religious influences of Persian conceptions have redirected the Jewish culture and religion.